The Impact of Prescribed Ozone in Climate Projections Run With HadGEM3‐GC3.1. (8th November 2019) - Hardiman, Steven C.; Andrews, Martin B.; Andrews, Timothy; Bushell, Andrew C.; Dunstone, Nick J.; Dyson, Harold; Jones, Gareth S.; Knight, Jeff R.; Neininger, Erica; O'Connor, Fiona M.; Ridley, Jeff K.; Ringer, Mark A.; et al.
Abstract: The Coupled Model Intercomparison Project 6 protocol suggests prescribing preindustrial ozone concentrations in abrupt‐4xCO2 simulations. This leads to a mismatch between the thermal tropopause, which rises due to climate change, and the ozone tropopause, which remains fixed. The result is unphysically high ozone concentrations in the upper troposphere, leading to a warm bias in cold point temperature and increased stratospheric water vapor. In the U.K. physical climate model HadGEM3‐GC3.1 this increases the surface climate sensitivity. In the future, other climate models without interactive ozone schemes may face similar problems. We describe a method to interactively redistribute ozone in climate simulations, which removes the inconsistency between the thermal and ozone tropopause heights while retaining the prescribed ozone distribution as closely as possible. This removes unphysical consequences of the tropopause mismatch, while still allowing a fair comparison against other Coupled Model Intercomparison Project 6 model simulations. After each model year, the monthly mean, zonal mean, thermal tropopause is formed based on the previous two model years. The ozone tropopause is defined at 1 km below the thermal tropopause by setting ozone concentrations there to 80 ppbv, and smoothing appropriately. The mass of ozone removed from the troposphere is added to the stratosphere thus conserving the total mass of ozone. This redistribution is then applied proportionally to the 3‐D monthly mean ozone concentrations. The climate model is run for the following year, using this redistributed ozone, and then the whole process is repeated. Results are presented from preindustrial and abrupt‐4xCO2 simulations, but this method can be used for any climate simulation. Key Points: Prescribed ozone in climate projections leads to unphysical ozone amounts in the upper troposphere These impact stratospheric water vapor and surface temperature Simple ozone redistribution is able to remove these impacts